Excessive focus on risk? Non-performing loans and efficiency of microfinance institutions - Stephen Zamore; Leif Atle Beisland; Roy Mersland (International Journal of Finance & Economics, 2021)
Microfinance is a banking market in which operating costs are high, while non-performing loans (NPLs) rates are low. While the existing literature tends to explain that the high operating costs arise from the provision of small loans, we argue that excessive efforts to control loan losses can also be a contributing factor. Therefore, this article investigates the relationship between NPLs and the cost efficiency of microfinance institutions (MFIs). Using a unique global sample of rated MFIs and applying stochastic frontier analysis together with Granger-causality test and generalized method of moments (GMM), we find, in contrast to positive linear relationship evidence in commercial banking studies, a nonlinear (U-shape) relationship between operating costs and NPLs. This implies that MFIs need to balance their cost efficiency with asset quality.
Keywords: 650